On the *-representation of one class of algebras associated with Coxeter graphs - Popova, N. D.; Samoilenko, Yu. S.; Strilets, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We investigate *-representations of a class of algebras that are quotient algebras of the Hecke algebras associated with Coxeter graphs. A description of all unitarily nonequivalent irreducible *-representations of finite-dimensional algebras is given. We prove that only trees that have at most one edge of type s > 3 define algebras of finite Hilbert type for all values of parameters.